2010
DOI: 10.1371/journal.pone.0011368
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dimorphism of the Zebra Finch Syrinx Indicates Adaptation for High Fundamental Frequencies in Males

Abstract: BackgroundIn many songbirds the larger vocal repertoire of males is associated with sexual dimorphism of the vocal control centers and muscles of the vocal organ, the syrinx. However, it is largely unknown how these differences are translated into different acoustic behavior.Methodology/Principal FindingsHere we show that the sound generating structures of the syrinx, the labia and the associated cartilaginous framework, also display sexual dimorphism. One of the bronchial half rings that position and tense th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 43 publications
1
53
0
Order By: Relevance
“…Many descriptions of voiced sound production are based on the seminal work by Titze (1988Titze ( , 1994, who described a model to account for the vocal folds motion in humans. Given the anatomical and functional similarities between the vocal apparatus of humans and birds (Riede and Goller, 2010), this description helps to capture essential features of birdsong production. Direct endoscopic observation showed that phonation was initiated in the songbird syrinx when two soft tissue masses, the medial and lateral labia, were pushed into the bronchial lumen (Goller and Larsen, 1997).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Many descriptions of voiced sound production are based on the seminal work by Titze (1988Titze ( , 1994, who described a model to account for the vocal folds motion in humans. Given the anatomical and functional similarities between the vocal apparatus of humans and birds (Riede and Goller, 2010), this description helps to capture essential features of birdsong production. Direct endoscopic observation showed that phonation was initiated in the songbird syrinx when two soft tissue masses, the medial and lateral labia, were pushed into the bronchial lumen (Goller and Larsen, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…6), a vocal tract model is required. In our biomechanical model, the trachea is modeled as a tube and the oroesophageal cavity is modeled as a Helmholtz resonator (Riede et al, 2006;. Two equations for the tube and glottis and three linear ordinary differential equations account for the dynamics of the airflow and pressure of the vocal tract , resulting in the final output pressure.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among temperate songbird species, vocalizations are generally limited to males and to contexts of territory defense and reproduction (Catchpole & Slater, 2008;Kroodsma & Miller, 1996). Male songbirds have a larger syrinx than females, despite similar body size, indicating sexual selection for more robust vocalizations (Riede, Fisher, & Goller, 2010). Further, female zebra finches, for example, have only rudimentary versions of certain song-learning and song-production telencephalon areas and produce only innate vocalization patterns (Nottebohm & Arnold, 1976).…”
Section: Heightened Sociality and The Vocal Repertoirementioning
confidence: 99%